Method of parallel implementation of wavelet transform using residue number system - Nikolay Ivanovich Chervyakov; Pavel Alekseyevich Lyakhov; Diana Ivanovna Kalita; Kirill Sergeyevich Shulzhenko (Наука. Инновации. Технологии)
The paper considers the use of wavelet filters based on the residue number system for complex improvement of the technical characteristics of wavelet signal processing devices using the residue number system. An important problem in the practical use of systems with low power consumption are signal distortions, that can significantly affect the quality of the signal being processed and cause an error in the operation of the system. The concept of implementing digital devices based on the residue number system and wavelet processing of signals is proposed with the aim of increasing the speed and reducing power consumption. Modeling on programmable logic integrated circuits of various families is carried out. The proposed concept allows to improve energy consumption parameters by 24% and speed by 21% for digital ilters in systems with low power consumption based on the residue numbersystem.